Relations of existential characteristics and hardiness with psychosomatic cardiac symptoms in young people - P. E. Grigoriev; I. V. Vasilieva (Бюллетень сибирской медицины, 2018)
Objective. Evaluation of the psychological well-being and hardiness in adolescents with cardiac symptoms.Materials and methods. The study involved 80 people aged 18–24 years, a relatively healthy sample. To assess the existential characteristics, the scale of psychological well-being of С. Ryff in the adaptation of N.N. Lepeshinsky. To assess the psychological quality of hardiness, the S. Maddi questionnaire was used in adaptation D.A. Leontiev, E.I. Rasskazova. To assess the psychosomatic component of cardiac symptoms the Giessen questionnaire of psychosomatic complaints was used. Descriptive statistics methods, the Mann – Whitney test for independent samples, a one-way analysis of variance with a posteriori pairwise comparison using the Newman-Keuls test were used.Results. For members of the healthy sample at the age of 18–24 years, the severity of psychosomatic cardiac complaints is relatively homogeneous by sex and age; the most significant differences in existential characteristics and hardiness in connection with the severity of psychosomatic cardiac symptoms fall on indicators of “commitment”, “control”, “environmental management”. Conclusion. The most significant and discriminating contribution to the prevention of psychosomatic cardiac complaints is such existential and stress-coping characteristics of personality as the ability to effectively use life situations to achieve one’s own goals, to fight for success and get results from their actions, to strive for maximum involvement in the activities of interest for the reflected, conscious meaning in life.